Bone marrow derived cell-seeded extracellular matrix: A novel biomaterial in the field of wound management - V. Remya; Naveen Kumar; A. K. Sharma; Dayamon D. Mathew; Mamta Negi; S. K. Maiti; Sameer Shrivastava; S. Sonal; N. P. Kurade (Veterinary World, 2014)
Aim: Extensive or irreversible damage to the skin often requires additional skin substitutes for reconstruction. Biomaterials have become critical components in the development of effective new medical therapies for wound care. Materials and Methods: In the present study, a cell matrix construct (bone marrow-derived cells (BMdc) seeded extracellular matrix [ECM]) was used as a biological substitute for the repair of full-thickness skin wound. ECM was developed by decellularizing fish swim bladder (FSB). Goat bone marrow-derived cells (G-BMdc) were seeded over this decellularized matrix. Efficacy of this cell matrix construct in wound repair was tested by implanting it over 20 mm2 × 20 mm2 size fullthickness skin wound created over the dorsum of rat. The study was conducted in 16 clinically healthy adult rats of either sex. The animals were randomly divided into 2 equal groups of 8 animals each. In Group I, animal’s wounds were repaired with a cellular FSB matrix. In Group II, wounds were repaired with G-BMdc seeded a cellular FSB matrix. Immune response and efficacy of healing were analyzed. Results: Quality of healing and immuno tolerance to the biological substitute was significantly better in Group II than Group I. Conclusion: Seeding with BMdc increases the wound healing potency and modulates the immune response to a significantly negligible level. The BMdc seeded acellular FSB matrix was found to be a novel biomaterial for wound management.